2020
DOI: 10.4025/actascianimsci.v42i1.48066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics and Yucca schidigera extract supplementation on broiler meat quality

Abstract: The current study investigated the effect of dietary supplementation with probiotics and Yucca schidigera extract on physicochemical parameters, proximate composition, mineral content and fatty acid profile of broiler breast and thigh muscles. In total, 240 one-day old broilers were randomly allocated into two dietary treatments groups: 1) Control (basal diet), 2) experimental (basal diet with two probiotics Pediococcus acidilactici and Saccharomyces cerevisiae and Yucca schidigera extract). The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
(32 reference statements)
4
10
1
Order By: Relevance
“…Wang et al [155] observed the decline in pH, however, pH24h (6.01) was increased by S. cerevisiae supplementation in relation with the control (5.80). Similar results have reported the inclusion in the diet of S. cerevisiae [156] and mixture Pediococcus acidilactici and S. cerevisiae [157]. Other studies showed that yeast products or culture improved the meat quality of broilers and pigs by decreasing the yellowness and stabilizing the pH of meat [102,158,159].…”
Section: Meat Qualitysupporting
confidence: 72%
See 1 more Smart Citation
“…Wang et al [155] observed the decline in pH, however, pH24h (6.01) was increased by S. cerevisiae supplementation in relation with the control (5.80). Similar results have reported the inclusion in the diet of S. cerevisiae [156] and mixture Pediococcus acidilactici and S. cerevisiae [157]. Other studies showed that yeast products or culture improved the meat quality of broilers and pigs by decreasing the yellowness and stabilizing the pH of meat [102,158,159].…”
Section: Meat Qualitysupporting
confidence: 72%
“…In cooking loss in broiler no difference was reported, regardless of probiotic feeding levels [165,168,169]. Also, the drip, cooking, and thaw losses on breast muscle were not observed by Benamirouche et al [157]. However, some studies observed that heat stress increases drip and cooking loss [79,144] of the breast meat [167].…”
Section: Meat Qualitymentioning
confidence: 86%
“…Similarly, Zhou et al [29] reported that dietary supplementation of oligosaccharides lowered the SFA proportion in the breast muscle of broilers. Furthermore, Benamirouche et al [30] reported decreased SFAs and increased UFAs in the breast meat of broilers fed with S. cerevisiae. Therefore, the proposed feed additive may contribute to lower de novo fatty acid synthesis and thus increase the UFA-to-SFA ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Benamirouche et al . [ 30 ] reported decreased SFAs and increased UFAs in the breast meat of broilers fed with S. cerevisiae . Therefore, the proposed feed additive may contribute to lower de novo fatty acid synthesis and thus increase the UFA-to-SFA ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [65] found that prebiotic supplementation can increase linoleic acid contents but decrease arachidonic acid contents in chicken breast meat; no effect on PUFA levels was observed. Stearic and SFA proportions decreased whereas linoleic and PUFA contents increased in breast and thigh meat of broilers fed probiotics and cassava extracts [98]. A definitive mechanism to explain the effect of dietary probiotics on the regulation of palmitic acid contents in chicken breast meat has been proposed.…”
Section: Discussionmentioning
confidence: 99%